Androgenic to oestrogenic switch in the human adult prostate gland is regulated by epigenetic silencing of steroid 5α‐reductase 2. Issue 4 (17th November 2017) - Wang, Zongwei; Hu, Libing; Salari, Keyan; Bechis, Seth; Ge, Rongbin; Wu, Shulin; Rassoulian, Cyrus; Pham, Jonathan; Wu, Chin‐Lee; Tabatabaei, Shahin; Strand, Douglas W; Olumi, Aria F
Abstract: Benign prostatic hyperplasia is the most common proliferative abnormality of the prostate. All men experience some prostatic growth as they age, but the rate of growth varies among individuals. Steroid 5α‐reductase 2 (SRD5A2) is a critical enzyme for prostatic development and growth. Previous work indicates that one‐third of adult prostatic samples do not express SRD5A2, secondary to epigenetic modifications. Here we show that the level of oestradiol is dramatically elevated, concomitant with significant upregulation of oestrogen response genes, in prostatic samples with methylation at the SRD5A2 promoter. The phosphorylation of oestrogen receptor‐α in prostatic stroma is upregulated when SRD5A2 expression is absent. We show that tumour necrosis factor (TNF)‐α suppresses SRD5A2 mRNA and protein expression, and simultaneously promotes expression of aromatase, the enzyme responsible for conversion of testosterone to oestradiol. Concomitant suppression of SRD5A2 and treatment with TNF‐α synergistically upregulate the aromatase levels. The data suggest that, in the absence of prostatic SRD5A2, there is an androgenic to oestrogenic switch. These findings have broad implications for choosing appropriate classes of medications for the management of benign and malignant prostatic diseases. Copyright © 2017 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.